Natural born heroes : how a daring band of misfits mastered the lost secrets of strength and endurance - McDougall, Christopher, 1962- (Alfred A. Knopf, 2015)
"Author of the phenomenal national best seller, Born to Run, Christopher McDougall now travels to the Mediterranean where he discovers that the secrets of ancient Greek heroes are still alive and well on the island of Crete and in the muscles and minds of fitness enthusiasts everywhere. While researching Born to Run, Chris McDougall encountered the story of Pheidippides, the legendary ancient Greek 'all-day runner.' Later, when McDougall met a dedicated amateur historian, he saw a connection to one of the most fascinating mysteries of World War II: How did a small band of Resistance fighters surrounded by German troops kidnap a top German general? What he discovered is that ancestral techniques for extraordinary endurance, natural movement, and nutrition allowed ancient Greek soldiers and Cretan shepherds to race across mountains on all-night missions. Inspired by their heroic acts, McDougall sets off to discover the lost art of the hero, both throughout history and across the world. Just as Born to Run inspired casual runners to get off the treadmill, out of their shoes, and into nature, Natural-Born Heroes will inspire casual athletes to leave the gym and take their fitness to nature doing cross-training, mud runs, parkour and free-running to bound--and climb, swim, skip, wade, and jump--their way to heroic feats"--